Modulation index and phase imbalance of Dual-Sideband Optical Carrier Suppression (DSB-OCS) in optical millimeter-wave system - Yaakob, Syamsuri; Mahmood, Rawa Muayad; Zan, Zuraidah; Mohd Rashidi, Che Beson; Mahmud, Azwan; Ahmad Anas, Siti Barirah (MDPI, 2021)
This paper presents a Dual-sideband Optical Carrier Suppression (DSB-OCS) technique which is used to generate an optical millimeter-wave (mm-wave) signal in radio over fiber (RoF) systems. The proposed system employs a Dual-Electrode Mach-Zehnder Modulator (DE-MZM) and a carrier of 40 GHz mm-wave for data transmission through the RoF systems. Characteristics determining the performance of the system, among which are the modulation index, phase imbalance and dispersion parameters, are included. The performance evaluations of the system show that the mm-wave signal output power follows MZM’s transfer function when the modulation index is raised. Moreover, the generated optical mm-wave signal power is affected by phase imbalance and optical splitting ratio. It is observed that the optical fiber dispersion influences the DSB-OCS system by decreasing the amplitude of the mm-wave and the signal-to-noise ratio (SNR).